Effectiveness of a Positive Parental Practices Training Program for Chilean Preschoolers’ Families: A Randomized Controlled Trial - Rincón, Paulina; Cova, Félix; Saldivia, Sandra; Bustos, Claudio; Grandón, Pamela; Inostroza, Carolina; Streiner, David; Bühring, Vasily; King, Michael (Frontiers in Psychology, 2018)
Background: Evidence for the effectiveness of parental training as a strategy for promotion of positive parental practices and prevention of child behavior problems in low and middle income countries is not conclusive. This study aims to assess the effectiveness of a universal positive parental training program designed for this context, “Día a Día” UdeC © (“Day by Day” University of Concepcion), in Chilean preschoolers’ families (3 to 6 years old children). Methods: A cluster randomized controlled trial (cRCT) was carried out in 19 preschool education centers. There were two treatment arms: 10 centers (including 178 families) were randomly assigned to the intervention group and 9 centers (including 154 families) were assigned to the waiting list control condition. Intervention groups received Day by Day UdeC, a six group sessions program for parents, including two group sessions for preschool educators, focused in affective communication; daily and child-directed play; directed attention; routines and transitions; reinforcement and incentive programs; planned inattention-ignore and time out; and logical consequences. Parental practices, parental satisfaction and presence of children behavioral problems were examined at two-time points: T1 (four weeks before intervention) and T2 (five to six weeks after intervention). Results: Intention-to-treat analysis shows a reduction in physical punishment and an increase in parental involvement, as well as a reduction in children behavioral problems. A per-protocol analysis revealed an additional effect: increase in observed parental practices. Conclusion: This cRCT provided evidence for the effectiveness of a parental training program for the promotion of positive parental practices in low and middle income countries. The observed effects of the program in decreasing physical punishment and children’s behavioral problems make it a promising strategy for prevention purpuses. Trial Registration: This study was registered under ISRCTN.com (ISRCTN90762146; https://doi.org/10.1186/ISRCTN90762146).